Tumor-infiltrating plasmacytoid dendritic cells are associated with survival in human colon cancer - Kießler, Maximilian; Pleșca, Ioana-Mădălina; Sommer, Ulrich; Wehner, Rebekka; Wilczkowski, Friederike; Müller, Luise; Tunger, Antje; Lai, Xixi; Rentsch, Anke; Peuker, Kenneth; Zeissig, Sebastian; Seifert, Adrian M.; et al. (Journal for ImmunoTherapy of Cancer, 2021)
Background Plasmacytoid dendritic cells (pDCs) play a key role in the induction and maintenance of antitumor immunity. Conversely, they can act as tolerogenic DCs by inhibiting tumor-directed immune responses. Therefore, pDCs may profoundly influence tumor progression. To gain novel insights into the role of pDCs in colon cancer, we investigated the frequency and clinical relevance of pDCs in primary tumor tissues from patients with colon cancer with different clinicopathological characteristics. Methods Immunohistochemical stainings were performed to explore the frequency of tumor-infiltrating BDCA-2+ pDCs in patients with colon cancer. Statistical analyses were conducted to determine an association between the pDC density and clinicopathological characteristics of the patients. Furthermore, we used multiplex immunofluorescence stainings to evaluate the localization and phenotype of pDCs in stroma and tertiary lymphoid structures (TLS) of colon cancer tissues. Results An increased density of infiltrating pDCs was associated with lower Union for International Cancer Control (UICC) stages. Furthermore, a higher pDC frequency was significantly correlated with increased progression-free and overall survival of patients with colon cancer. Moreover, a lower number of coloncancer-infiltrating pDCs was significantly and independently linked to worse prognosis. In addition, we found that a proportion of pDCs shows a nuclear expression of the transcription factor interferon regulatory factor 7 (IRF7), which is characteristic for an activated phenotype. In various tumor stroma regions, IRF7+ pDCs were located in the neighborhood of granzyme B-expressing CD8+ T cells. Moreover, pDCs were identified as a novel component of the T cell zone of colon cancer-associated TLS, which are major regulators of adaptive antitumor immunity. A proportion of TLS-associated pDCs displayed a nuclear IRF7 expression and was preferentially located close to CD4+ T cells. Conclusions These results indicate that higher densities of tumor-infiltrating pDCs are associated with prolonged survival of patients with colon cancer. Moreover, colon cancer-infiltrating pDCs may represent a novel prognostic factor. The colocalization of activated pDCs and T cells in tumor stroma and within TLS may contribute to the correlation between higher pDC densities and better prognosis. In addition, our findings may have implications for the design of novel immunotherapeutic strategies that are based on targeting colon cancer-infiltrating pDCs.
Gesehen am 26.06.2021